Identifying Bereavement‐Related Markers of Mental and Behavioral Health Problems Among Clinic‐Referred Adolescents. Issue 2 (16th December 2020) - Kaplow, Julie B.; Wamser‐Nanney, Rachel; Layne, Christopher M.; Burnside, Amanda; King, Cheryl; Liang, Li‐Jung; Steinberg, Alan; Briggs, Ernestine; Suarez, Liza; Pynoos, Robert
Abstract : Objective: This study examined bereavement‐related risk markers (number of deaths, cause of death, and relationship to deceased) of mental and behavioral health problems (suicidal thoughts or behaviors, self‐injury, depression, posttraumatic stress, and substance use) in a national sample of clinic‐referred bereaved adolescents. Method: Participants included 1281 bereaved youth aged 12–21 years (M=15, SD=1.8; 62.1% female), from the National Child Traumatic Stress Network Core Data Set. Results: Generalized linear mixed‐effects regression models controlling for demographics and other traumas revealed that youth bereaved by multiple deaths had higher posttraumatic stress scores than youth bereaved by a single death (Estimated difference ±SE=3.36 ± 1.11, p=0.003). Youth bereaved by suicide were more likely to report experiencing suicidal thoughts or behaviors (AOR=1.68, p=0.049) and alcohol use (AOR=2.33, p<0.001) than youth bereaved by natural causes. Youth bereaved by homicide were at greater risk for substance use than youth bereaved by natural death (AOR=1.76, p=0.02). Compared to parentally bereaved youth, youth who lost a peer were more likely to use alcohol (AOR=2.32, p=0.02) or other substances (AOR=2.41, p=0.01); in contrast, parentally bereaved youth were more likely to experience depression compared to those who experienced the death of an adult relative or unrelated adult (range of AOR: 0.40 to 0.64, p‐values<0.05). Conclusion: These bereavement‐related contextual factors can serve as early markers of mental and behavioral health problems among bereaved youth. HIGHLIGHTS: Few studies have examined bereavement‐related risk markers of mental and behavioral health problems among treatment‐seeking adolescents. Number of prior traumas, number of prior losses, experiencing a death due to suicide or homicide, and experiencing the death of a parent (as opposed to another relative or friend) were each associated with higher levels of mental and behavioral health problems among bereaved adolescents. Findings have implications for early identification of bereaved youth who may be in need of intervention.